2004
DOI: 10.1007/bf03215520
|View full text |Cite
|
Sign up to set email alerts
|

Scope for new applications for gold arising from the electrocatalytic behaviour of its metastable surface states

Abstract: The electrocatalytic behaviour of gold in aqueous media is surprisingly complex and a novel view of gold electrode surfaces is proposed to explain the observed electrochemical responses. The metal surface is considered as a chemically (or redox) modified electrode, with equilibrated, low energy, surface gold atoms functioning as a relatively inert support and low coverage, high energy, protruding gold atoms (or minute clusters of same) functioning as electrocatalytic redox mediators. The protruding atoms are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 42 publications
(37 reference statements)
10
102
0
1
Order By: Relevance
“…However, numerous studies have shown that gold is not as inert as its d 10 configuration suggests which accounts for its pronounced catalytic and electrocatalytic activity [6,[17][18][19][20][21][22][23][24]. This has been attributed to active sites on the surface that consists of atoms or clusters of atoms that have low co-ordination number and have the ability to partake in electrocatalytic reactions [21,22,25,26]. Recent work by Scholz has demonstrated in the case of gold that active or defect sites are located on the asperities of an electrode surface which are the loci of partially filled d orbitals that can stabilise free radical intermediates [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous studies have shown that gold is not as inert as its d 10 configuration suggests which accounts for its pronounced catalytic and electrocatalytic activity [6,[17][18][19][20][21][22][23][24]. This has been attributed to active sites on the surface that consists of atoms or clusters of atoms that have low co-ordination number and have the ability to partake in electrocatalytic reactions [21,22,25,26]. Recent work by Scholz has demonstrated in the case of gold that active or defect sites are located on the asperities of an electrode surface which are the loci of partially filled d orbitals that can stabilise free radical intermediates [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that the activity of electrodes (and of heterogeneous catalysts) is associated with surface defects [1][2][3][4][5][6][7][8][9]; platinum black is a familiar example [10]. In contrast, deactivation is typically achieved by "brute-force" methods such as total passivation [11,12].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Therefore, 0.1 M solutions of H 2 SO 4 , HClO 4 , HNO 3 , and HCl were chosen as the possible electrolytes. Among them, HCl was the best choice for Fe(III) detection because Cl − can be adsorbed on the AuNPs in the potentials more positive than 0.0 V, which may increase the electron transfer by bridging mechanism [31]. Because the pH value of HCl is an important factor affecting the signal response of Fe(III), the effect of the pH value of the solution on the electrochemical response of 10 μM Fe(III) at the rGO/MB/ AuNPs composite modified GCE was examined in various HCl solution at pH of 2.97, 1.99, and 0.98, respectively.…”
Section: The Effect Of Electrolytes and Ph Valuesmentioning
confidence: 99%